Pendekatan Uses And Gratification Theory pada Penerapan Teknologi Informasi dan Komunikasi di Sekolah Dasar - Meisi Isnaini; Akhmad Habibi; Muhammad Sofwan (Departement of Mathematics Education, 2023)
The need for information is one of a person's needs, because it is very important to expand knowledge. The presence of information and communication technology makes it easy for every use, especially in the field of education. Education can be utilized by teachers and students in the learning process. Information and communication technology can be used by teachers as a medium that helps improve the quality of learning. This study aims to determine the effect of the Uses and Gratification Theory (UGT) approach to the use of ICT by teachers in the learning process. To achieve this goal, data was collected from 130 teachers in 3 elementary schools in Jambi city through a survey with a questionnaire aimed at teachers who had integrated Information and Communication Technology, which were then analyzed using PLS-SEM. The results showed that the Uses and Gratification Theory (UGT) approach consisting of cognitive needs, affective needs, and social needs is valid and influences the use of Information and Communication Technology by teachers in primary schools in Jambi city in the learning process, effective and used as needed.